Polarized training is optimal for endurance athletes - Foster, C.; Casado, A.; Esteve-Lanao, J.; Haugen, T.; Seiler, S. (Medicine & Science in Sports & Exercise, 2022)
The potential advantages of a more polarized (including pyradimal) TID for endurance athletes, particularly during the precompetitive period, have emerged over decades, with evidence favoring polarized TID more evident in the ob servational literature, and evidence favoring pyramidal TID more evident in the experimental literature. This TID model proposes that the relative proportion of training effort should be organized relative to lactate/ventilatory thresholds along the general plan that 70%-80% of either training hours or ses sions are conducted below the intensity of the first lactate/ ventilatory threshold. Abundant observational and interven tional data support the concept that this TID has advantages over threshold centric training programs, with the best de signed of the intervention studies (18,21) providing the stron gest evidence. The underlying physiological causes for this ap parent advantage remain to be determined but may relate to differences in both the pattern and magnitude intracellular adaptive signaling (particularly that amplifying mitochondrial synthesis) and to prevention of autonomic dysfunction and/or inflammatory responses associated with excessive higher intensity training. The polarized/pyradimal TID may be particu larly important for elite athletes, with high training frequency/ load and a greater risk of training maladaptations (7). Less ac complished athletes with lower training frequency/load are less likely to experience negative effects from threshold centric train ing, although our collective experience still supports the value of an approach to training dominated by a TID favoring low intensity training.